Performance of Sesame(Sesamumindicum L.) Varieties Under Varied Nutrient Levels - Malek, M; Ali, MH; Karim, MF; Ullah, MJ; Paul, AK; Masum, SM (Bangladesh Agronomy Journal, 2022)
The study was carried out to evaluate some sesame varieties under different nutrient levels for enhancing the productivity of sesame during March – June, 2014. The experiment was carried out in a split-plot design with three replications. The main -plot treatments had four nutrient levels viz., 75% of the recommended dose of fertilizer(RDF), 100% RDF, 125% of RDF, and 150% of RDF, and the sub - plot treatments included six sesame varieties viz., Laltil (Local), Atshira (Local), T6, BARI Til-3, BARI Til-4 and Binatil-2. RDF indicates a nutrient schedule of 56:72:23 kg N, P2O5, and K2O ha-1. The effect of nutrient levels, varieties, and their interaction showed significant variation in respect of yield contributing parameters, yield, and harvest index. Results revealed that in nutrient levels, 100% of RDF produced the highest seed yield (1223 kg ha-1). The least seed yield was observed with 150% of RDF (924 kg ha-1). Among the sesame varieties,BARI Til-4 showed the optimum growth and yield contributing parameters as a result highest seed yield (1170 kg ha-1). The lowest seed yield was obtained from Laltil (811.30 kg ha-1). The interaction effect was found significant where highest seed yield of 1481 kg ha-1 with 100% of RDF combination of sesame var. BARI Til-4. Bangladesh Agron. J. 2021, 24(2): 31-41